Is the “Minimally Conscious State” Patient Minimally Self-Aware? - Picolas, Constantinos (Frontiers in Psychology, 2020)
Patients in a Minimally Conscious State (MCS) constitute a subgroup of awareness impaired patients who show minimal signs of awareness as opposed to patients in a Vegetative State who do not exhibit any such signs. While the empirical literature is rich in studies investigating either overt or covert signs of awareness in such patients the question of self-awareness has only scarcely been addressed. Even in the occasion where self-awareness is concerned, it is only higher-order or reflective self-awareness that is the target of such investigations. In the first part of this paper, I briefly review part of the relevant clinical neuroscience literature to demonstrate that the conception of self-awareness at play in such studies is indeed that of reflective self-awareness. In the second part, I present the philosophical notion of pre-reflective (or minimal) self-awareness. This is shown to primarily refer to the implicit awareness of our embodied subjectivity which essentially permeates all our experiences. As discussed, this minimal self-awareness is not specifically addressed when clinically or experimentally assessing patients in MCS. My suggestion is that neuroimaging studies targeting minimal self-awareness as in First-Person Perspective-taking paradigms could be used with MCS patients to shed light on the question of whether those individuals are minimally self-aware even in the case where they lack self-reflective abilities. Empirical evidence of this kind could have important theoretical implications for the discussion about the notion of self-awareness but also potential medical and social/legal implications for awareness impaired patients' management.